2007
DOI: 10.1111/j.1471-4159.2007.04915.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced neuronal nitric oxide synthase is involved in ischemia‐induced hippocampal neurogenesis by up‐regulating inducible nitric oxide synthase expression

Abstract: Nitric oxide (NO), a free radical with signaling functions in the CNS, is implicated in some developmental processes, including neuronal survival, precursor proliferation, and differentiation. However, neuronal nitric oxide synthase (nNOS) -derived NO and inducible nitric oxide synthase (iNOS) -derived NO play opposite role in regulating neurogenesis in the dentate gyrus after cerebral ischemia. In this study, we show that focal cerebral ischemia reduced nNOS expression and enzymatic activity in the hippocampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 54 publications
(84 reference statements)
3
73
0
2
Order By: Relevance
“…Recently, it has been demonstrated that NO pathway controls CREB-mediated gene expression in neurons (Riccio et al, 2006). Consistent with our previous findings that nNOS inhibition elevated hippocampal pCREB levels in vivo (Zhu et al, 2006;Luo et al, 2007), we showed here that nNOS-derived NO suppressed CREB phosphorylation in vitro, indicating an implication of nNOS in CREB phosphorylation. Because deletion of nNOS abolished the 5-HT 1A R-mediated CREB activation and behaviors and, more importantly, CREB phosphorylation was essential for the behavioral effect of nNOS inhibition, it is very likely that CREB activation is critical for the roles of 5-HT 1A R-nNOS pathway.…”
supporting
confidence: 80%
“…Recently, it has been demonstrated that NO pathway controls CREB-mediated gene expression in neurons (Riccio et al, 2006). Consistent with our previous findings that nNOS inhibition elevated hippocampal pCREB levels in vivo (Zhu et al, 2006;Luo et al, 2007), we showed here that nNOS-derived NO suppressed CREB phosphorylation in vitro, indicating an implication of nNOS in CREB phosphorylation. Because deletion of nNOS abolished the 5-HT 1A R-mediated CREB activation and behaviors and, more importantly, CREB phosphorylation was essential for the behavioral effect of nNOS inhibition, it is very likely that CREB activation is critical for the roles of 5-HT 1A R-nNOS pathway.…”
supporting
confidence: 80%
“…Nitric oxide exerts a dual effect on neurogenesis: While nNOS-derived NO decreases neurogenesis (Packer et al, 2003;Moreno-Lopez et al, 2004;Zhu et al, 2006), NO produced by endothelial (Reif et al, 2004) or inducible (Luo et al, 2007;Bechade et al, 2011) NOS seems to stimulate it.…”
Section: Nitric Oxide-physiologymentioning
confidence: 99%
“…Treatment with iNOS inhibitor aminoguanidine prevented postischemic neurogenesis ; the phenomenon could not be detected in iNOS null mice, either . Nitric oxide produced by nNOS exerts negative effects on neurogenesis (Packer et al, 2003;Moreno-Lopez et al, 2004;Luo et al, 2007), nNOS inhibition has been shown to increase neurogenesis after experimental ischemia (Sun et al, 2005). Neuronal NOS and iNOS therefore seem to have opposite roles in postischemic neurogenesis.…”
Section: Nitric Oxide-pathophysiology In Strokementioning
confidence: 99%
“…This has been demonstrated both in developmental and in adult neurogenesis in the two brain areas, the hippocampal subgranular zone of the dentate gyrus and the subventricular zone of the lateral ventricles, that maintain lifelong neurogenetic activity [118][119][120][121][122][123][124]. However, multiple experimental evidences suggest that NO may instead stimulate neurogenesis in the hippocampal dentate gyrus following different types of damage and that activated microglia is primarily responsible for the NO overproduction under these conditions [125][126][127][128][129][130]. This iNOS-related microglia action can be interpreted as a mechanism helping the recovery of neural function after damage.…”
Section: Nitric Oxide In the Cross-talk Between Microglia And Neuronsmentioning
confidence: 99%